Kounis syndrome in a patient with secondary mast cell activation syndrome after a bee sting - Aytekin, Gokhan; Colkesen, Fatih; Yildiz, Eray; Arslan, Sevket; Oltulu, Pembe (Annals of Medical Research, 2021)
None